Inventarisasi Hama dan Penyakit Tanaman Hortikultura di Sriwijaya Science Techno Park Sumatera Selatan - Karenina, Tili; Tania Defriyanti, Wenni; Yesi, Desri; Novriadhy, Dian; Efriandi, Efriandi (Seminar Nasional Lahan Suboptimal, 2022)
Karenina T, Defriyanti WT, Yesi D, Novriadhy D, Efriandi E. 2022. Inventory of pests and diseases oh horticultural plants in sriwijaya science techno park of South Sumatera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang  27 Oktober 2022. pp. 513-523. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The attack of plant pests is one of the limiting factors in the cultivation of horticultural crops in Sriwijaya Science Techno Park. Knowledge and monitoring of pests and diseases early can be an alternative control that can reduce crop yield loss economically. This study aimed to inventory and evaluate pest and disease control measures for horticultural crops at the Sriwijaya Science Techno Park site. The research was conducted at a horticultural crop cultivation site at the Sriwijaya Science Techno Park in March 2021. This research was conducted by field observation methods and literature studies. The results showed that 6 species of pests and 6 symptoms of plant disease attacks were found in the cultivation of horticultural crops (bitter gourd, red chili, long beans, tomatoes, bengkoang, and eggplant) at sriwijaya Science Techno Park. Pest and disease control with the application of synthetic pesticides had not paid attention to the exact dosage, method, and time of application. Knowledge and monitoring of pests are necessary to determine effective and efficient control techniques.